Electrolyte material for all-solid-state battery and all-solid-state battery including the same

The electrolyte material comprising a lithium salt and an electrophilic molecule with a specific molar ratio addresses the challenges of low ionic conductivity and processing difficulties in solid electrolytes for all solid-state batteries, achieving enhanced lithium ion mobility and conductivity.

JP7657925B2Active Publication Date: 2025-04-07LG ENERGY SOLUTION LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023526644
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-25
Filing Date
2022-03-23
Publication Date
2025-04-07
Estimated Expiration
2042-03-23

AI Technical Summary

Technical Problem

Existing solid electrolytes for all solid-state batteries face challenges in achieving high ionic conductivity while also presenting difficulties in manufacturing and processing due to the complexity of mixing and processing high-melting-point components.

Method used

The development of an electrolyte material composed of a lithium salt and an electrophilic molecule, where the electrophilic molecule is an electrically neutral compound containing oxygen atoms with a chemical resonance structure, such as benzoquinone-based compounds, and the lithium salt includes LiFSI, LiTFSI, or other lithium salts, with a molar ratio of electrophilic molecule to lithium salt ranging from 1 to 3.

Benefits of technology

This electrolyte material achieves an ionic conductivity of 1×10^-3 S/cm at room temperature, which is higher than previous solid electrolytes, making it easier to manufacture and process, and enhancing the mobility of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657925000001
    Figure 0007657925000001
  • Figure 0007657925000002
    Figure 0007657925000002
  • Figure 0007657925000003
    Figure 0007657925000003
Patent Text Reader

Abstract

The present invention relates to an electrolyte material for an all-solid-state battery, which is composed of a lithium salt and an electrophilic molecule. The solid electrolyte material according to the present invention has high ionic conductivity and exhibits improved manufacturing and processing characteristics. l
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolyte material for an all-solid-state battery and an all-solid-state battery including the same.

[0002] This application claims priority to Korean Patent Application No. 10-2021-0039179, filed on March 25, 2021, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]

[0003] Solid electrolytes are broadly divided into polymer, oxide, and sulfide types. Polymer electrolytes have the disadvantage of relatively low ionic conductivity, but compared to oxide or sulfide solid electrolytes, they have low contact resistance at the interface with the active material, making the battery manufacturing process easier, and their low density is advantageous for increasing the energy density of batteries. Polymer electrolytes were first discovered in the 1970s by PV Wright's group that PEO (polyethylene oxide) polymers form complexes with alkali salts and have ionic conductivity, and M. Armand and others began to apply them to lithium batteries and electrochemistry. Polymer electrolytes have a low glass transition temperature, so the movement of polymer chains at room temperature should be active, and they should contain hetero elements such as oxygen, nitrogen, and sulfur that can donate electrons to smoothly dissociate lithium salts. As candidate materials for polymer electrolytes that meet these conditions, have high ionic conductivity, and have strong mechanical strength, polymers such as PEO, PAN (polyacetonitrile), PDMS (polydimethylsiloxane), PMMA (polymethylmethacrylate), and PVdF (polyvinylidenefluoride) have been studied. Among them, research on PEO-based polymer electrolytes has been particularly active, but only a small number of studies have been conducted on the PEO-based polymer electrolytes, which have a melting point of 10 -5 The low ionic conductivity of 1.0 S / cm has limited its commercial application.

[0004] Polymer electrolytes are broadly divided into dry polymer electrolytes, which are made up of polymers and lithium salts, and gel polymer electrolytes, which contain liquid components as additives. Gel polymer electrolytes are stable at about 10 -4 ~10 -3 It has an ionic conductivity of 10 ...

[0005] Meanwhile, the prior patent US9,742,000B2 discloses a solid electrolyte based on a PPS (Polyphenylene sulfide) polymer, which has an ionic conductivity of 1×10 at room temperature. -3 S / cm level. According to the patent, the polymer electrolyte is composed of PPS, dopant, and lithium salt, and the polymer is in a glassy state at room temperature. The higher the crystallinity of the polymer, the better the ionic conductivity, and it is presumed that the formation of a charge transfer complex between the polymer and dopant is a factor in inducing the mobility of lithium ions. In a rubbery state, lithium ions move due to the segmental motion of the polymer, which is in stark contrast to PEO-based polymer electrolytes, in which the lower the crystallinity of the polymer, the higher the ionic conductivity.

[0006] PPS-based polymer electrolyte is a ternary electrolyte consisting of PPS, dopant, and lithium salt, and each component is a solid with a high melting point. It is difficult to mix and process each component when manufacturing a solid electrolyte, so it has a disadvantage of being difficult to realize ion conductivity. Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention aims to provide an electrolyte material for an all-solid-state battery having high ionic conductivity and improved manufacturing and processing characteristics. Meanwhile, other objects and advantages of the present invention will be understood from the following description and will be more clearly understood from the examples of the present invention. In addition, the objects and advantages of the present invention can be realized by the means and combinations thereof shown in the claims. [Means for solving the problem]

[0008] The present invention relates to an electrolyte material for an all-solid-state battery.

[0009] A first aspect of the present invention relates to an electrolyte material for an all-solid-state battery, the electrolyte material being composed of a lithium salt and an electrophilic molecule, The electrophilic molecule is a compound that is electrically neutral, contains an oxygen atom (O) in its molecular structure, and has a chemical resonance structure; The lithium salts include LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiBETI (lithium bis(pentafluoroethanesulfonyl)imide), LiCTFSI (LiN(C 2 F 4 S 2 O 4 )), LiN(CN) 2 , LiBF 4 , LiClO 4 , LiPF 6 , Li(CF 3 )2 PF 4 , Li(CF 3 ) 3 PF 3 , Li(CF 3 ) 4 PF 2 , Li(CF 3 ) 5 PF, Li(CF 3 ) 6 P, LiCF 3 SO 3 , LiCF 3 CF 2 SO 3 , LiCF 3 CF 2 (CF 3 ) 2 CO, Li(CF 3 SO 2 ) 2 CH, (SF 5 ) 3 C, Li(CF 3 SO 2 ) 3 C, LiCF 3 (CF 2 ) 7 SO 3 , LiCF 3 CO 2 , LiCH 3 CO 2 , LiSCN or two or more of these.

[0010] According to a second aspect of the present invention, the electrophilic molecule comprises a benzoquinone-based compound.

[0011] According to a third aspect of the present invention, in the second aspect, the benzoquinone-based compound has one or more hydrogen atoms each independently substituted with a functional group having a cyano group (CN), chlorine (Cl) or bromine (Br).

[0012] According to a fourth aspect of the present invention, in any one of the first to third aspects, the electrophilic molecule includes benzoquinone, 2,3-dicyano-5,6-dichlorobenzoquinone (DDQ), chloranil, bromanil, p-chloranilic acid, or two or more thereof.

[0013] According to a fifth aspect of the present invention, in any one of the first to fourth aspects, the lithium salt includes LiFSI, LiTFSI, LiBETI, LiCTFSI, or two or more thereof.

[0014] According to a sixth aspect of the present invention, in any one of the first to fifth aspects, a molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is 1-3.

[0015] According to a seventh aspect of the present invention, in any one of the first to sixth aspects, the electrophilic molecule comprises one or more benzoquinone-based compounds, the lithium salt comprises LiFSI, LiTFSI, LiBETI, LiCTFSI or two or more thereof, and a molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is 0 to 3.

[0016] According to an eighth aspect of the present invention, in any one of the first to seventh aspects, the electrolyte material contains LiTFSI as a lithium salt and chloranil as an electrophilic molecule.

[0017] According to a ninth aspect of the present invention, in the eighth aspect, the electrolyte material contains LiTFSI as a lithium salt and chloranil as an electrophilic molecule, and a molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is 1 to 3.

[0018] The present invention relates to an electrochemical element including the electrolyte material for an all-solid-state battery according to the present invention, the electrochemical element including a negative electrode, a positive electrode, and a solid electrolyte membrane interposed between the negative electrode and the positive electrode, and at least one of the negative electrode, the positive electrode, and the solid electrolyte membrane includes the electrolyte material according to the present invention. Effect of the Invention

[0019] The electrolyte material of the present invention has an ionic conductivity of 1×10 -3 It has a hardness of more than S / cm and is easy to manufacture and process.

[0020] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention, and serve to further understand the technical ideas of the present invention together with the detailed description of the invention, and therefore the present invention should not be interpreted as being limited to the matters described in the drawings. In addition, the shape, size, scale, ratio, etc. of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]

[0021] [Figure 1] This is a model for a CHL / LiTFSI binary electrolyte material obtained by AIMD (Ab initio molecular dynamics) simulation, in which lithium (Li), oxygen (O), carbon (C), sulfur (S), nitrogen (N), fluorine (F), and chlorine (Cl) atoms are distinguished. [Figure 2a] This figure shows the change in the coordination number of oxygen atoms (O) around lithium depending on the CHL / LiTFSI ratio for the CHL / LiTFSI binary electrolyte material generated by AIMD simulation. [Figure 2b] This figure shows the change in the coordination number of oxygen atoms (O) around lithium depending on the CHL / LiTFSI ratio for the CHL / LiTFSI binary electrolyte material generated by AIMD simulation. [Figure 2c]This figure shows the change in the coordination number of oxygen atoms (O) around lithium depending on the CHL / LiTFSI ratio for the CHL / LiTFSI binary electrolyte material generated by AIMD simulation. [Figure 3a] FIG. 1 shows the lithium ion diffusion coefficient as a function of temperature in a CHL / LiTFSI solid electrolyte. [Figure 3b] FIG. 1 shows the TFSI anion diffusion coefficient as a function of temperature in the CHL / LiTFSI solid electrolyte. [Figure 4a] FIG. 1 shows the concentration of LiTFSI according to the CHL / LiTFSI ratio. [Figure 4b] FIG. 1 is a graph showing the ionic conductivity of solid electrolytes depending on the CHL / LiTFSI ratio. [Figure 5a] This is a diagram showing partial charges by NCHL / NTFSI. [Figure 5b] FIG. 1 shows the lithium separation energy by NCHL / NTFSI. [Figure 6a] 1 is a graph showing the number of sites to which lithium ions can hop depending on the CHL / LiTFSI ratio. [Figure 6b] 1 is a table showing the number of sites to which lithium ions can hop depending on the CHL / LiTFSI ratio. [Figure 7] The chemical formulas showing the structures of DDQ, chloranil, bromanil, and p-chloranilic acid. [Figure 8] 1 is a table showing the number of CHL and LiTFSI molecules according to the CHL / LiTFSI ratio in a supercell used in an AIMD (ab initio molecular dynamics) simulation. [Figure 9] 1 is a table showing the lithium ion diffusion coefficient, the TFSI anion diffusion coefficient, and the transport number of lithium cations at room temperature (25° C.) according to the CHL / LiTFSI ratio. [Figure 10]The ionic diffusion rate D of Li+ at the CHL-LiTFSI / PPS interface was calculated and shown with the change in the thickness of the CHL-LiTFSI layer. [Figure 11] 1 is a table showing a comparison of ionic conductivity between an example (CHL / LiTFSI) and a comparative example (CHL / LiTFSI / PPS). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the embodiment described in this specification and the configuration shown in the drawings are only one most preferred embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted for them at the time of this application.

[0023] In addition, throughout the specification, when a part "comprises" or "includes" certain elements, this does not mean that other elements are excluded, but that other elements may also be included, unless otherwise specified.

[0024] The terms "about," "substantially," and the like, used throughout this specification, when given the meaning inherent in the manufacturing and material tolerances, are used to mean a numerical value or a approximation thereof, and are used to prevent unconscionable infringers from unfairly using disclosures in which precise or absolute numerical values ​​are recited to aid in the understanding of this application.

[0025] Throughout this specification, the phrase "A and / or B" means "A or B, or all of these."

[0026] Certain terminology is used in the following detailed description for convenience only and is not limiting. The words "right", "left", "top" and "bottom" designate directions in the drawings to which reference is made. The words "inward" and "outward" designate directions toward or away from the geometric center of the designated device, system and components thereof, respectively. "Front", "rear", "upper", "lower" and related words and phrases designate locations and orientations in the drawings to which reference is made and are not limiting. Such terms include the example words above, derivatives thereof and words of similar import.

[0027] The present invention relates to an electrolyte material for an all-solid-state battery. The present invention also relates to an all-solid-state battery comprising the electrolyte material.

[0028] In one embodiment of the present invention, the electrophilic molecule is preferably electrically neutral and has a molecular structure in which oxygen (O), which strongly interacts with Li, is bonded to a benzene aromatic group as a functional group, so that the distribution of electrons can achieve chemical resonance. The electrophilic molecule may exhibit properties of an electron acceptor and / or an oxidant.

[0029] In one embodiment of the present invention, the electrophilic molecule may include one or more benzoquinone-based compounds. When one or more hydrogens H of the benzoquinone are replaced with a functional group having a chlorine (Cl), bromine (Br) or cyano group (CN), the electrophilicity may be maximized and the electrophilicity may exhibit a stronger interaction with lithium.

[0030] In one embodiment of the present invention, the electrophilic molecule is benzoquinone, 2,3-dicyano-5,6-dichlorobenzoquinone (C 8 C l2 N 2 O 2 )(DDQ), tetrachloro-1,4-benzoquinone (C 6 Cl 4 O 2 The chlorination agent may include one or more selected from Chloranil, Bromanil and p-Chloranilic acid.

[0031] In one embodiment of the present invention, the lithium salt is LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiBETI (lithium bis(pentafluoroethanesulfonyl)imide), LiCTFSI (LiN(C 2 F 4 S 2 O 4 )), LiN(CN) 2 , LiBF 4 , LiClO 4 , LiPF 6 , Li(CF 3 ) 2 PF 4 , Li(CF 3 ) 3 PF 3 , Li(CF 3 ) 4 PF 2 , Li(CF 3 ) 5 PF, Li(CF 3 ) 6 P, LiCF 3 SO 3 , LiCF 3 CF 2 SO 3 , LiCF 3 CF 2 (CF 3 ) 2 CO, Li(CF 3 SO 2 ) 2 CH, (SF 5 ) 3 C, Li (CF 3 SO 2 ) 3 C, LiCF 3 (CF 2 ) 7 SO 3 , LiCF 3 CO 2 , LiCH 3 CO 2 , LiSCN, or two or more of these.

[0032] Preferably, the lithium salt includes LiFSI, LiTFSI, LiBETI, LiCTFSI, or two or more thereof.

[0033] In one embodiment of the present invention, when the electrophilic molecule includes one or more benzoquinone-based compounds, the molar ratio of the electrophilic molecule to the lithium salt in the electrolyte material (electrophilic molecule / lithium salt) may be 1 to 3. Specifically, the molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) may be, for example, 1 to 2 or 2 to 3. In terms of ionic conductivity of the electrolyte material, the molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is desirably 1 to 2.

[0034] In a further specific embodiment of the present invention, when the electrophilic molecule includes one or more benzoquinone-based compounds and the lithium salt includes one or more of LiFSI, LiTFSI, LiBETI, and LiCTFSI, the molar ratio of the electrophilic molecule to the lithium salt in the electrolyte material (electrophilic molecule / lithium salt) may be 1 to 3. Specifically, the molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) may be, for example, 1 to 2 or 2 to 3. In terms of ionic conductivity of the electrolyte material, the molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is preferably 1 to 2.

[0035] In order for an electrolyte material to exhibit lithium ion conductivity, lithium ions must be mobile within the electrolyte material, and to achieve this, mobile lithium ions must be generated and there must be hopping sites to which the lithium ions can migrate.

[0036] In the electrolyte material composed of the electrophilic molecule / lithium salt of the present invention, the lithium ion conductivity based on the mutual attraction between molecules is affected by the coupling between an atom with high electrophilicity, such as oxygen of the electrophilic molecule, and the lithium atom of the lithium salt. In the absence of the electrophilic molecule, the lithium atom in the lithium salt, such as LiTFSI, is strongly coordinated by the oxygen atom of the lithium salt, and there is no hopping site, which is a vacancy site where lithium can hop. In the case of LiTFSI, the lithium atom is strongly coordinated by four oxygen atoms of TFSI. However, in the electrolyte material composed of the electrophilic molecule and the lithium salt, such as chloranil, the oxygen atoms of the lithium salt surrounding the lithium are gradually replaced by the oxygen atoms of the electrophilic molecule, and the Li-O binding force is weakened, and the Li-O coordination number is reduced. As a result, a free oxygen atom (Li-free O) that is not bound to lithium is generated to form an oxygen (O) cage, and such an oxygen cage can be provided as a hopping site where lithium ions can hop. That is, when a lithium salt and an electrophilic molecule are mixed, as the molar ratio of the electrophilic molecule to the lithium salt increases, the lithium separation energy decreases and the number of sites to which the lithium ions can hop increases, thereby making the lithium ions more mobile, and thus improving the ionic conductivity of the electrolyte material in proportion to the increase.

[0037] In one embodiment of the present invention, the electrolyte material may include CHL (chloranil) as an electrophilic molecule and LiTFSI as a lithium salt. As described above, as the CHL / LiTFSI molar ratio in the electrolyte material increases, the lithium ions become more mobile, and the ionic conductivity of the electrolyte material increases proportionately. In the case of a two-component electrolyte material of CHL / LiTFSI, even if the amount of CHL containing two oxygen atoms (O) in one molecular structure increases, the total coordination number (CN) of Li-O does not exceed 4. Instead, the number of free oxygen atoms (referred to as "Free O") that are not coordinated to Li increases, and O cages composed of Free O provide sites to which lithium ions can hop. This enables vacancy-mediated Li ion migration with a relatively low activation energy.

[0038] Based on the two-component electrolyte material of CHL / LiTFSI, the role of the electrophilic molecule based on its molecular structure can be explained as follows.

[0039] CHL has a structure in which six H atoms of benzene are replaced by four Cl atoms and two O atoms. This structure is basically electrophilic, more electrophilic than benzoquinone because of the Cl atoms. CHL acts as an electron acceptor, and Li acts as an electron donor. When O and Li of CHL interact, the transferred electron is delocalized and stabilized in the chemical resonance structure formed by the aromatic ring and the C=O group.

[0040] The charge polarization between Li and O in CHL forms Li-O coordinate bonds, which are not stronger than the Li-O bond in LiTFSI. Therefore, when electrophilic molecules with chemical resonance groups form binary electrolyte materials with lithium salts, they can exhibit high ionic conductivity as electrolyte materials for all-solid-state batteries.

[0041] The present invention also provides an all-solid-state battery including the electrolyte material described above. The all-solid-state battery includes a positive electrode, a negative electrode, and a solid electrolyte membrane, and at least one of the positive electrode, the negative electrode, and the solid electrolyte membrane may include the electrolyte material having the above-described characteristics.

[0042] In one embodiment of the present invention, the solid electrolyte membrane is an ion-conductive sheet that is interposed between a positive electrode and a negative electrode in an all-solid-state battery and acts as an insulator and an ion-conductive channel, and preferably has a thickness of 1.0×0 -5 The solid electrolyte membrane contains the electrolyte material according to the present invention and may further contain other electrolyte materials described below.

[0043] In the present invention, the positive electrode and the negative electrode each include a current collector and an electrode active material layer formed on at least one surface of the current collector, and the active material layer includes a plurality of electrode active material particles and an electrolyte material. The positive electrode and the negative electrode may include the electrolyte material according to the present invention as the electrolyte material, and may further include other electrolyte materials described below.

[0044] In addition, each electrode may further include at least one of a conductive material and a binder resin, if necessary, and may further include various additives for the purpose of complementing or improving the physicochemical properties of the electrode.

[0045] In the present invention, the negative electrode active material may include lithium metal as a negative electrode active material of a lithium ion secondary battery, and any other material that can be used as a negative electrode active material may be used. For example, the negative electrode active material may be carbon such as non-graphitizable carbon and graphite-based carbon; Li x Fe2 O 3 (0 ≦ x ≦ 1), Li x WO 2 (0 ≦ x ≦ 1), Sn x Me 1-x Me’ y O z (Me: Mn, Fe, Pb, Ge; Me’: Al, B, P, Si, Group 1, 2, 3 elements of the periodic table, halogen; 0 < x ≦ 1; 1 ≦ y ≦ 3; 1 ≦ z ≦ 8) and other metal composite oxides; lithium alloys; silicon-based alloys; tin-based alloys; SnO, SnO 2 , PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi 2 O 3 , Bi 2 O 4 , and Bi 2 O 5 and other metal oxides; conductive polymers such as polyacetylene; Li-Co-Ni-based materials; titanium oxides; lithium titanium oxides, etc. may further be included, one or more selected therefrom.

[0046] When the electrode is a positive electrode, the electrode active material can be used without limitation as long as it can be used as a positive electrode active material of a lithium-ion secondary battery. For example, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ) or a compound substituted with one or more transition metals; the chemical formula Li 1+x Mn 2-x O 4 (where x is 0 to 0.33).), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 and other lithium manganese oxides; lithium copper oxide (Li 2CuO 2 );LiV 3 O 8 , LiV 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-x M x O 2 (wherein M=Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x=0.01 to 0.3); Ni-site type lithium nickel oxide represented by the chemical formula LiMn 1-x M x O 2 (wherein M=Co, Ni, Fe, Cr, Zn or Ta, and x=0.01 to 0.1) or Li 2 Mn 3 MO 8 (wherein M=Fe, Co, Ni, Cu or Zn); Lithium manganese composite oxide represented by LiNi x Mn 2-x O 4 Lithium manganese oxide with a spinel structure represented by the formula LiMn 2 O 4 ;Disulfide compounds;Fe 2 (MoO 4 ) 3 These may include, but are not limited to, the following:

[0047] In the present invention, the current collector may be an electrically conductive metal plate or the like, and may be any suitable current collector according to the polarity of the current collector electrode known in the field of secondary batteries.

[0048] In the present invention, the conductive material is usually added in an amount of 1% by weight to 30% by weight based on the total weight of the mixture including the electrode active material. Such a conductive material is not particularly limited as long as it has conductivity without inducing chemical changes in the battery. For example, the conductive material may include one or a mixture of two or more conductive materials selected from graphite such as natural graphite and artificial graphite; carbon black-based carbon materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; metal powders such as carbon fluoride, aluminum, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and polyphenylene derivatives.

[0049] In the present invention, the binder resin is not particularly limited as long as it is a component that assists in binding the active material and the conductive material and binding to the current collector. For example, polyvinylidene fluoride polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber, fluororubber, various copolymers, etc. The binder resin may be generally contained in a range of 1% by weight to 30% by weight, or 1% by weight to 10% by weight, based on 100% by weight of the electrode layer.

[0050] In the present invention, each of the electrode active materials may contain one or more additives such as an oxidation stabilizing additive, a reduction stabilizing additive, a flame retardant, a heat stabilizer, an antifogging agent, etc., if necessary.

[0051] In the present invention, the all-solid-state battery may include the solid electrolyte material according to the present invention as a solid electrolyte material, and may further include at least one of a polymer-based solid electrolyte, an oxide-based solid electrolyte, and a sulfide-based solid electrolyte.

[0052] The polymer solid electrolyte is a composite of lithium salt and polymer resin, i.e., a polymer electrolyte material formed by adding polymer resin to a solvated lithium salt, and has a capacity of about 1×10 -7 S / cm or more, preferably about 1×10 -5 It can exhibit ionic conductivity of 0.1 S / cm or more.

[0053] Non-limiting examples of the polymer resin include polyether polymers, polycarbonate polymers, acrylate polymers, polysiloxane polymers, phosphazene polymers, polyethylene derivatives, alkylene oxide derivatives such as polyethylene oxide (PEO), phosphate polymers, polyagitation lysine, polyester sulfide, polyvinyl alcohol, polyvinylidene fluoride, polymers containing ionic dissociation groups, etc., and may include at least one of these. In addition, the polymer electrolyte may include, as a polymer resin, branched copolymers in which an amorphous polymer such as PMMA, polycarbonate, polysiloxane (pdms) and / or phosphazene is copolymerized with a comonomer on a PEO main chain, comb-like polymers, crosslinked polymer resins, etc., and may include at least one of these.

[0054] In the electrolyte of the present invention, the lithium salt is an ionizable lithium salt, and Li + X - The anion of such a lithium salt is not particularly limited, but may be F - , Cl - , Br - , I - , NO 3 - , N(CN) 2 - , B.F. 4 - , ClO 4 - , P.F. 6 - , (CF 3 ) 2 PF 4 -, (CF 3 ) 3 PF 3 - , (CF 3 ) 4 PF 2 - , (CF 3 ) 5 PF - , (CF 3 ) 6 P - , CF 3 SO 3 - , CF 3 CF 2 SO 3 - , (CF 3 SO 2 ) 2 N - , (FSO 2 ) 2 N - , CF 3 CF 2 (CF 3 ) 2 CO - , (CF 3 SO 2 ) 2 CH - , (SF 5 ) 3 C - , (CF 3 SO 2 ) 3 C - , CF 3 (CF 2 ) 7 SO 3 - , CF 3 CO 2 - , CH 3 CO 2 - , SCN - , (CF 3 CF 2 SO 2 ) 2 N - and the like can be mentioned.

[0055] The oxide-based solid electrolyte material contains oxygen O and has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table. Non-limiting examples of this include LLTO-based compounds, Li 6 La 2 CaTa 2 O 12 , Li 6 La 2 ANb 2 O 12 (A is Ca or Sr), Li 2 Nd 3 TeSbO 12 , Li 3 BO 2.5 N 0.5 , Li 9 SiAlO 8 , LAGP compounds, LATP compounds, Li 1+x Ti 2-x Al x S y (PO 4 ) 3-y (where 0≦x≦1, 0≦y≦1), LiAl x Zr 2-x (PO 4 ) 3 (where 0≦x≦1, 0≦y≦1), LiTi x Zr 2-x (PO 4 ) 3 (where 0≦x≦1, 0≦y≦1), the compound may include at least one selected from the group consisting of LISICON-based compounds, LIPON-based compounds, perovskite-based compounds, Nasicon-based compounds, and LLZO-based compounds, but is not limited thereto.

[0056] The sulfide-based solid electrolyte material contains sulfur (S) and has the ionic conductivity of a metal belonging to Group 1 or Group 2 of the periodic table, and may include Li-PS-based glass and Li-PS-based glass ceramic. Non-limiting examples of such sulfide-based solid electrolytes include Li 2 SP 2 S 5 , Li 2 S-LiI-P 2 S 5 , Li 2 S-LiI-Li 2 OP2 S 5 , Li 2 S-LiBr-P 2 S 5 , Li 2 S-Li 2 OP 2 S 5 , Li 2 S-Li 3 PO 4 -P 2 S 5 , Li 2 SP 2 S 5 -P 2 O 5 , Li 2 SP 2 S 5 -SiS 2 , Li 2 SP 2 S 5 -SnS, Li 2 SP 2 S 5 -Al 2 S 3 , Li 2 S-GeS 2 , Li 2 S-GeS 2 -ZnS, etc., and may contain one or more of these. However, the present invention is not limited to these.

[0057] The present invention also provides a secondary battery having the above-mentioned structure. The present invention also provides a battery module including the secondary battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source. Specific examples of the device include, but are not limited to, a power tool that is driven by power from a battery-type motor; electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc.; electric two-wheeled vehicles including electric bicycles (E-bikes) and electric scooters (E-scooters); electric golf carts; and power storage systems.

[0058] [Example] In order to generate a model of a binary electrolyte material composed of CHL (Chloranil) and LiTFSI, an AIMD (ab initio molecular dynamics) simulation was performed, and the ionic conductivity of the electrolyte material was calculated using computational chemistry. In the simulation, the CHL / LiTFSI ratio was applied as 0, 1, 2, and 3, and the number of CHL and LiTFSI molecules in the supercell for each composition is shown in Figure 8.

[0059] For better statistical treatment, three other model structures were generated for each CHL / LiTFSI ratio. Before every production run, the bulk electrolyte system was subjected to volumetric equilibration in the NPT ensemble at 300 K under 1 atm, and AIMD simulations were performed for the canonical NVT ensemble using a Nose-Hoover thermostat. Each simulation supercell was annealed at 700 K for 5 ps (type step 1 fs) to ensure rapid local structural rearrangement, and then cooled to 350 K at a rate of 0.7 K / fs. After the cooling process, each binary electrolyte material was further optimized by conjugate-gradient energy minimization using density-functional theory calculations.

[0060] Figure 1 shows a molecular arrangement model for a CHL / LiTFSI two-component electrolyte material obtained by AIMD simulation. In Figure 1, lithium (Li), oxygen (O), carbon (C), sulfur (S), nitrogen (N), fluorine (F) and chlorine (Cl) are each shown separately. Figure 2a shows the molecular arrangement around lithium when the CHL / LiTFSI molar ratio is 0, 1, 2 and 3, respectively. In Figure 2a, N CHL and N TFSI indicate the number of CHLs and TFSIs adjacent to lithium, respectively.

[0061] In FIG. 1, it can be seen that the lithium atom is surrounded by oxygen atoms (O) of TFSI or oxygen atoms (O) of CHL. In this case, the oxygen atoms around Li are O CHL , O TFSI-A and O.T. FSI-B Here, O CHL indicates the two oxygen atoms present in CHL, and O TFSI-Aindicates two oxygen atoms in TFSI directly bonded to the same lithium, and O TFSI-B indicates the remaining two oxygen atoms present in TFSI.

[0062] Referring to FIG. 2a, when the molar ratio of CHL:LiTFSI is 0:1, Li is surrounded by three TFSIs through bonds with four oxygen atoms. That is, the four oxygen atoms around Li are connected to two O atoms present in the same TFSI. TFSI-A and one each of two different TFSIs TFSI-B The total number of oxygen atoms (O) coordinated around Li is called the total coordination number (CN Total : Total coordination number) and CN TFSI-A , C.N. TFSI-B , C.N. CHL Each of the O surrounding a lithium atom TFSI-A , O TFSI-B , O CHL When CHL=0, that is, when only LiTFSI is used as the electrolyte, the total coordination number of Li atoms, CN Total is 4, and more specifically, CN TFSI-A =2, CN TFSI-B =2, CN CHL = 0. Figure 2b shows the molecular arrangement of a model with NCHL = 1 and NTFSI = 2, and CN TFSI-A , C.N. TFSI-B and C.N. CHL are CN TFSI-A =2, CN TFSI-B =1,CN CHL =1.

[0063] In order to obtain statistical information on the interaction between lithium and oxygen atoms surrounding lithium, a coordination number analysis was performed on the CHL / LiTFSI binary electrolyte material. For each lithium, the O atom corresponding to the first peak of the RDF (Radial Distribution Function) for the Li-O pair was assumed to be coordinated to Li.

[0064] In Figure 2c, CN TFSI-A , C.N. TFSI-B , C.N. CHL and C.N. total As shown in Figure 2c, as the CHL / LiTFSI ratio increases, the total coordination number and the O coordination number of TFSI decrease, while the O coordination number of CHL increases. Specifically, as the CHL / LiTFSI ratio increases from 0 to 3, the average coordination number of CN CHL increases from 0 and converges to about 1.3, and CN TFSI-B has decreased from 2 to about 0.62. However, CN TFSI-A does not show a substantial decrease when the CHL / LiTFSI ratio increases from 0 to 2 (CN TFSI-A The values ​​of 2.0, 1.9 and 1.7 were observed, respectively. When the CHL / LiTFSI ratio exceeded 2, CN TFSI-A The value was 1.08 and was confirmed to decrease rapidly.

[0065] From the above results, it was inferred that when the CHL / LiTFSI ratio is less than about 2, the coordination of Li-OTFSI-B is replaced by the coordination of Li-CHL, while when the CHL / LiTFSI ratio is more than about 2, the coordination of Li-OTFSI-A is replaced by the coordination of Li-CHL. LITFSI is decomposed into Li cations and TFSI anions, and CN TFSI-A Considering the decrease in , it was confirmed from the above results that dissociation of lithium salts is more likely to occur when the CHL / LiTFSI ratio exceeds about 2:1.

[0066] Meanwhile, the ionic conductivity was calculated by molecular dynamics (MD) simulation for solid composite electrolytes with CHL / LiTFSI molar ratios adjusted to 0, 1, 2, and 3. The diffusion coefficients of lithium cations and TFSI anions were calculated by MSD (mean square displacement) analysis, and the ionic conductivity was calculated from the diffusion coefficients using the Nernst-Einstein equation.

[0067] If the MSD is calculated at room temperature in order to obtain the diffusion coefficients of lithium cations and TFSI anions at room temperature, the simulation time would be too long. Therefore, in this calculation, the MSD was calculated at high temperatures (400K, 425K, 450K, 475K, 500K), the diffusion coefficients were calculated from the obtained MSD, and the diffusion coefficients at room temperature (25°C) were obtained using an Arrhenius plot.

[0068] The diffusion coefficients of lithium ions (FIG. 3a) and TFSI anions (FIG. 3b) are shown in FIG. 3a and FIG. 3b, respectively. When CHL / LiTFSI=0, the diffusion coefficients of lithium and TFSI were negligibly low and therefore were excluded from the figures.

[0069] Figure 4a shows the LiTFSI concentration as a function of the CHL / LiTFSI ratio. It was confirmed that the LiTFSI concentration per volume decreased as the chloranil content increased.

[0070] Figure 4b shows the ionic conductivity as a function of the CHL / LiTFSI ratio calculated from the diffusion coefficient. It can be seen that when the CHL / LiTFSI ratio increases from 1 to 2, the ionic conductivity increases, and when the CHL / LiTFSI ratio increases from 2 to 3, the ionic conductivity decreases.

[0071] Figure 9 shows the lithium cation conductivity (unit: S / cm) and TFSI anion ion conductivity (unit: S / cm) at room temperature (25°C) as a function of the CHL / LiTFSI ratio, as well as the ion conductivity of the entire electrolyte material and the transport number of lithium cations. The lithium cation conductivity is close to 0 in the absence of CHL, and increases significantly as CHL is added. As the CHL concentration relative to LiTFSI increases, the ion conductivity continues to increase, but because the Li concentration relative to the total volume decreases, it can be seen that the ion conductivity reaches its maximum when the CHL / LiTFSI molar ratio is around 2.

[0072] In Fig. 5a and Fig. 5b, N CHL / N TFSIThe partial charge and lithium separation energy for each CHL are shown. As the CHL concentration increases from 0 to 3, the lithium ion separation energy decreases, making it easier to dissociate the lithium salt.

[0073] Figures 6a and 6b show the number of hopping sites available for lithium ions depending on the CHL / LiTFSI ratio. It can be seen that as the CHL / LiTFSI ratio increases from 0 to 3, the number of hopping sites available for lithium ions increases from 0 to approximately 2. The sites available for lithium ions to hop are vacancy sites composed of O that is not coordinated with Li, and can also be called cages composed of O. This cage is composed of 3 to 4 O.

[0074] [Comparative Example] Lithium ion diffusion coefficient and ionic conductivity of CHL / LiTFSI / PPS ternary electrolytes. To confirm the effect of PPS on the ionic conductivity in the chloranil-LiTFSI ion-conducting channel, a PPS polymer (Mw 5486 g / mol) interface was formed in the ion-conducting channel layer of CHL:LiTFSI = 3:1, and the chloranil-LiTFSI / PPS interface effect was confirmed.

[0075] Figure 10 below shows the Li + The ion diffusion coefficient of the chloranil-LiTFSI ion-conducting channel in the slap structure is shown in Fig. 1. Here, Li + It can be seen that the ion diffusion coefficient of is greatly affected by the thickness of the chloranil-LiTFSI ion conduction channel, and the thicker the ion conduction channel, the higher the ion diffusion coefficient becomes, which means that the chloranil-LiTFSI / PPS interface has the effect of suppressing the diffusion of lithium ions.

[0076] As a result, it can be seen that the thick chloranil-LiTFSI ion-conducting channel exhibits improved ion conductivity compared to the thin chloranil-LiTFSI ion-conducting channel, as shown in FIGS.

[0077] The overall conductance in Figure 11 is calculated for an electrolyte area of ​​1 cm 2 This is the value when the thickness is 20 μm. This shows that polymers such as PPS are not essential components for ensuring ionic conductivity, and ionic conduction can easily occur in a two-component solid electrolyte material of lithium salt and electrophilic molecules even without a polymer component.

Claims

1. A two-component electrolyte material composed of a lithium salt and an electrophilic molecule, The electrophilic molecule is a compound that is electrically neutral, contains an oxygen atom (O) in its molecular structure, and has a chemical resonance structure; The lithium salt is LiFSI, LiTFSI, LiBETI, LiCTFSI (LiN(C 2 F 4 S 2 O 4 ))), LiN(CN) 2 , LiBF 4 , LiClO 4 , LiPF 6 , Li(CF 3 ), 2 PF 4 , Li(CF 3 ), 3 PF 3 , Li(CF 3 ), 4 PF 2 , Li(CF 3 ), 5 PF, Li(CF 3 ), 6 P, LiCF 3 SO 3 , LiCF 3 CF 2 SO 3 , LiCF 3 CF 2 (CF 3 ), 2 CO, Li(CF 3 SO 2 ), 2 CH, (SF 5 ), 3 C, Li(CF 3 SO 2 ), 3 C, LiCF 3 (CF 2 ), 7 SO 3 , LiCF 3 CO 2 , LiCH 3 CO 2 and includes one or more of these, the electrophilic molecule comprises a benzoquinone-based compound, The benzoquinone-based compound is an electrolyte material for an all-solid-state battery, in which one or more hydrogen atoms are each independently substituted with a functional group having a cyano group (CN), chlorine (Cl), or bromine (Br).

2. 2. The electrolyte material for an all-solid-state battery according to claim 1, wherein the electrophilic molecule comprises 2,3-dicyano-5,6-dichlorobenzoquinone (DDQ), chloranil, bromanil, p-chloranilic acid, or two or more thereof.

3. 3. The electrolyte material for an all-solid-state battery according to claim 1 or 2, wherein the lithium salt comprises LiFSI, LiTFSI, LiBETI, LiCTFSI, or two or more thereof.

4. 4. The electrolyte material for an all-solid-state battery according to claim 1, wherein a molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is 1 to 3.

5. 2. The electrolyte material for an all-solid-state battery according to claim 1, wherein the electrophilic molecule comprises one or more benzoquinone-based compounds, the lithium salt comprises LiFSI, LiTFSI, LiBETI, LiCTFSI, or two or more thereof, and a molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is 0 to 3.

6. 2. The electrolyte material for an all-solid-state battery according to claim 1, wherein the electrolyte material contains LiTFSI as a lithium salt and chloranil as an electrophilic molecule.

7. 7. The electrolyte material for an all-solid-state battery according to claim 6, wherein the electrolyte material contains LiTFSI as a lithium salt and chloranil as an electrophilic molecule, and a molar ratio of the electrophilic molecule to the lithium salt (electrophilic molecule / lithium salt) is 1 to 3.

8. 13. An all-solid-state battery comprising a negative electrode, a positive electrode, and a solid electrolyte film interposed between the negative electrode and the positive electrode, wherein at least one of the negative electrode, the positive electrode, and the solid electrolyte film comprises the electrolyte material according to claim 1.

Citation Information

Patent Citations

  • Composite solid electrolyte material and preparation method thereof

    CN111740157A

  • Solid bipolar battery

    JP2018521461A

  • Lithium secondary battery

    JP2019200880A

  • Polymer electrolyte sheet and manufacturing method thereof, and electrochemical device and manufacturing method thereof

    JP2020053229A

  • Polymer solid electrolyte composition and polymer membrane comprising the same

    KR1020180124546A